MENTAL HEALTH EMOTIONAL BEHAVIOR CONDITIONS OF PRESCHOOL AGE CHILDREN DURING THE COVID-19 PANDEMIC IN YOGYAKARTA - Ignasia Yunita Sari; Aprillyani Rika Susanti; Dolina Dolina; Herni Widiastuti; Januaria Sudiahartati (Jurnal Kesehatan Madani Medika (JKMM), 2021)
Background: he COVID -19 pandemic has prompted a very drastic change in relationships as social beings. According to UNICEF (2020) there are 80 million children in Indonesia (about 30% of the entire population) who have the potential to experience serious problems due to the COVID-19 pandemic. More than 2.2 billion children in the world, which is about 28% of the world's child population, have experienced mental health changes as a result of the COVID-19 pandemic. Objective: To determine the Mental Health Condition of Emotional Behavior of Preschool Age Children during the COVID-19 Pandemic in Yogyakarta in 2021. Methods: The study used a descriptive design with a quantitative approach, the population of all preschool aged children in Yogyakarta amounted to 225.900 people. The research sample technique uses a sampling quota. The number of samples used was 153 respondents conducted in August 2021. Results: Emotional behavior problems in preschool age children, showed that at most there were no emotional problems, namely 94 respondents (61.4%) and children who experienced emotional behavior problems as many as 59 respondents (38 ,6%).